Chemical Compositions and Antioxidant Properties of Orange Fleshed Sweet Potato Leaves and the Consumer Acceptability in Vegetable Soup - Omoba, Olufunmilayo Sade (Prev Nutr Food Sci, 2020)
The purpose of this study is to determine the chemical compositions, anti-nutrient compositions, antioxidant properties, and phenolic profile of the leaves of orange fleshed sweet potato varieties [King J (UMUSPO1) and mother’s delight (UMUSPO2)] in Nigeria and their suitabilities in soup preparation. Freshly harvested leaves of the two varieties of orange fleshed sweet potato were sorted, cleaned, dried, and milled into powder. The dried leaves were assessed for their chemical compositions viz proximate and mineral compositions, the anti-nutrient compositions, antioxidant properties, and phenolic profile. The overall acceptability of the leafy vegetables in the preparation of a local soup (Edikang Ikong) was evaluated. The ash, fat, and protein contents of UMUSPO1 leaves were higher than UMUSPO2, similarly UMUSPO1 leaves had higher mineral contents. Phytate and saponin contents were higher in UMUSPO2, however, the calculated molar ratios were below critical levels. The 2,2-diphenyl-1-picrylhydrazyl hydrate radical scavenging activity and ferric reducing antioxidant power assay were higher in UMUSPO1. Seven phenolic compounds were identified and quantified in both leaves with gallic acid being the most abundant. The taste of soup prepared with UMUSPO2 was rated higher, however, no significant difference was observed in the overall acceptability of the soups. The two leaves are good sources of nutritional antioxidants and can be suitable for the management of some disease conditions linked to oxidative stress.